PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN KELOMPOK TANI DI DESA TANAH ABANG KECAMATAN LONG MESANGAT KABUPATEN KUTAI TIMUR (The Role of Agricultural Extension in the Development of Farmer Groups in Tanah Abang Village Long Mesanggat Subregency East Kutai Regency) - HESTININGSIH HESTININGSIH; JURAEMI JURAEMI; FIRDA JUITA (Universitas Mulawarman (University of Mulawarman), 2021)
Agricultural extension is a non-formal educational process that aims to improve the welfare of farmers. This study aimed to determine the role of Field Agricultural Extension (FAE) in the development of farmer groups. This research was conducted from March to May 2020 in Tanah Abang Village, Long Mesanggat Subregency, East Kutai Regency. Determination of samples number used a proportional sampling method with a total sample of 38 respondents. The data obtained were analyzed using descriptive statistics. The results showed the role of FAE is as a motivator, educator, and facilitator. Growing farmer groups in terms farmer group institutions become strong and independent, increasing members ability in agribusiness development, and increasing groups ability in carrying out its functions.